Study of the impact of gas flaring on communities’ health: methods and participants’ demographics - Obi, Nkemdilim; Bwititi, Phillip; Nwose, Ezekiel (International Journal of Scientific Reports, 2021)
The exploration and production of oil and gas in Nigeria have resulted in gas flaring. This has led to the release of excessive amounts of harmful pollutants possibly leading to ill-health, loss of lives and damage to properties in communities where gas is flared. This has resulted in various studies on the impact of gas flaring on the health of communities. This article described the methodology and demographics of respondents of research in Delta State Nigeria. This research was designed to be a cross-sectional mixed method study. About 500 self-administered questionnaires were distributed to individuals of 18 years and above and the response rate 97.4%. The questionnaire comprised six sections with closed and open-ended questions to ensure objectivity and accuracy of data. Demographic analysis showed that participants comprised 40.1% women, 99.1% reside in 12 oil-producing local government areas (LGA) across Delta State and 69.4% have lived in region for 3-20 years. On occupation, 97.7% work in communities distributed across oil-producing 11 LGAs and 68.2% have worked in the region for 3-20 years. Other participants lived and/or worked in neighbouring communities and states. Participants were well distributed in age groups with 89% consisting of 20-70 years old. Further, respondents comprised 96% who completed secondary or higher and 61.7% classified themselves as middle or upper-class socioeconomic status. The proposal has provision to generate nuanced perspectives of stakeholders. The distribution of respondents indicates satisfactory selection criteria for valid responses to survey questions.